Multiple Myeloma - Fuchs, Ota (IntechOpen, 2021)
This book deals with the diagnosis and treatment of multiple myeloma. Multiple myeloma is a plasma cell disorder, the prognosis of which has dramatically improved in the last years thanks to new immunomodulatory drugs, proteasome inhibitors, and monoclonal antibodies, in relapsed/refractory disease and a diagnosis. Chapters cover such topics as prognostic and predictive factors in newly diagnosed multiple myeloma, treatment approaches, antibody therapies, and three-dimensional (3D) models mimicking multiple myeloma bone marrow-microenvironment interactions.